Caracterización de lodos como inoculantes para un reactor anaeróbico para el tratamiento de vinaza - Machado, Walter D. (2016)
The implementation of a process of biological wastewater treatment requires knowledge of physicochemical andmicrobiological characteristics of the inoculum used, as well as the substrate to be treated.The aim of this work was to characterize sludge with methanogenic activity and vinasses for use as a substrate inanaerobic bio-digestion process.Five sludges of different sources were analyzed. The sludge from sacrifice´s lagoons of stillage, was chosenbecause it had higher concentrations of volatile suspended solids (26.13%) and higher methane production capacity (SpecificMethanogenic Activity, SMA = 0.15 gCODCH4/gSSV.d). The selection of an inoculum from the treatment of vinasse, shortensthe adaptation of microorganisms in the reactor. The characterization of vinasse consisted in determining the main parametersto study the nutrient ratio (COD:N:P) required to be used as substrate in a UASB type digester (upflow anaerobic sludgeblanket), in addition to the physicochemical parameters as pH and conductivity. It was determined that the analyzed vinassecovered with the requirements of nitrogen and organic matter, and phosphorus must be added to maintain the COD:N:P ratioin 500:7:1, suggested as optimal in the literature, to achieve granulation. The tests proposed to characterize the samples ofsludge obtained, allowed to establish some differences and criteria to select the inoculum for future tests.